Si Wire Supported MnO2/Al/Fluorocarbon 3D Core/Shell Nanoenergetic Arrays with Long-Term Storage Stability - Ying Zhu (Nature Portfolio, 2017)
Abstract Three-dimensional MnO2/Al/fluorocarbon core/shell nanoenergetic arrays are prepared on silicon substrate that is with silicon wires on top. Silicon wires are first prepared as the scaffolds by maskless deep reactive ion etching of silicon wafer, which is followed by the hydrothermal growth of MnO2. Al and fluorocarbon are then deposited sequentially around the silicon wire (Si-W) supported MnO2 arrays by magnetron sputtering to realize the core/shell nanoenergetic composite. Several characterization techniques are used to investigate the prepared Si-W/MnO2/Al/fluorocarbon arrays, including the scanning electron microscopy, transmission electron microscopy, energy dispersive spectroscopy, X-ray photoelectron spectroscopy, and thermal analysis. 3D upright aligned core/shell structure with an intimate contact between MnO2 and Al is confirmed from the morphological characterization. Superhydrophobicity is achieved after the fluorocarbon coating. Most importantly, the Si-W/MnO2/Al/fluorocarbon nanoenergetic arrays show no decay of energy density after 9 months of storage, indicating potential applications in nanoenergetics-on-a-chip when long-term storage is needed.